The effect of 4-week leg extension training on the strength of quadricaps muscles - Krisnan, L.; Hoo, L.K.; Lim, B.H.; Teo, E.W. (2014)
This study was conducted to identify the effect of 4-week leg extension training on the strength of quadriceps muscles. Thirty University of Malaya students (n = 30) consisting of fourteen male (n = 14) and sixteen female (n = 16); (age M = 20.33 ± 0.80 years: height M = 165.93 ± 8.75 cm; weight M = 61.12 ± 13.12 kg) who were recruited by using the method of random sampling. These subjects were equally divided into two groups, the experimental group (n = 15) and the control group (n = 15) which respectively with a total of fifteen subjects (male = 7; female = 8) in each group. The experimental group carried out eight sessions of leg extension training. The 1 repetition maximum (1RM) of quadriceps muscles for both groups was obtained twice; pre-test and post-test. The results revealed that eight sessions of leg extension training induced significant improvement (t = 1.97, df = 28, p<. 05) on the strength of quadriceps muscles. However, the results also revealed that the control group did not shown a significant difference in the strength of quadriceps muscles between pre and post intervention (t = 0.00, df = 14, p>.05). These results suggest that the four week leg extension training is an ~ffective and suitable method to improve the strength of quadriceps muscles.